PENGARUH KESIAPAN BELAJAR DAN DUKUNGAN SOSIAL TERHADAP PRESTASI BELAJAR MAHASISWA PASCA PANDEMI - Ulfah Wahidah; Yoni Hermawan; Gugum Gumilar (JOURNAL SAINS STUDENT RESEARCH, 2023)
The problem in this research concerns student learning achievement after the pandemic, where there is a decrease in student average IP/IPK scores after online learning. This research aims to determine the influence of learning readiness and social support on student learning achievement. The research method used in this research is a survey method with an explanatory design. The population in this research is Economic Education student Class of 2020 Faculty of Teacher Training and Education Siliwangi University with a total of 112 student. The sampling technique used is saturated sampling with a sample size of 112 respondens. Based on the research result, it is clear that 1) There is a positive and significant influence of learning readiness on student learning achievement with a ˃ (5,908 ˃ 1,982). 2) There is a positive and significant influence of social support on student learning achievement with ˃ (19,292 ˃ 1,982). 3) There is a positive and significant influence of learning readiness and social support on student learning achievement with ˃ (421,315 ˃ 3,08). The Conclusion of this research is that learning readiness and social support have a positive and significant effect on student learning achievement. Suggestion from this research are for student to pay more attention to learning readiness both physically and psychologically always concentrate on participating in learning activities so that they can easily improve their intellectual abilities and have achievement study which are expected.